Pengaruh Discarge Planning terhadap Pengetahuan Pengelolaan Nutrisi Pasien Diabetes Millitus Type II di RS PKU MUhammadiyah Yogyakarta - LAYUHIBU, Welsi (STIKES 'Aisyiyah Yogyakarta, 2015)
Background : Discharge planning is the provision of information to patients and families to know how to manage nutrients after being treated in Hospital, and know what the risk factors that can make the disease relapse and treatment at home later against the disease. Discharge planning aims to minimize the impact of a health condition such disease with continuous treatment. Purpose : This study was to fully assess the effect of discharge planning on nutrition knowledge management of patients with type II diabetes mellitus. Research method : This study made used pre experiment with one group preposttest